2005
DOI: 10.1038/sj.cgt.7700857
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference and potential therapeutic applications of short interfering RNAs

Abstract: RNA interference is an endogenous gene-silencing mechanism that involves double-stranded RNA-mediated sequence-specific mRNA degradation. The discovery of this pathway together with the elucidation of the structure and function of short interfering RNAs -the effector molecules of RNA interference -has had an enormous impact on experimental biology. RNA interference technologies are currently the most widely utilized techniques in functional genomic studies. Furthermore, there is an intense research effort aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 108 publications
0
77
0
1
Order By: Relevance
“…These findings indicate that HDAC inhibitor-mediated radiosensitization is associated with a decrease in the repair of DSBs. Furthermore, a recent study using TSA demonstrated an increase in the number of radiationinduced g-H2AX foci, suggesting that the change in chromatin structure caused by histone hyperacetylation results in an increase in the number of DSBs (Karagiannis et al, 2005).…”
Section: Mechanisms Of Hdac Inhibitor-mediated Enhanced Radiation Senmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings indicate that HDAC inhibitor-mediated radiosensitization is associated with a decrease in the repair of DSBs. Furthermore, a recent study using TSA demonstrated an increase in the number of radiationinduced g-H2AX foci, suggesting that the change in chromatin structure caused by histone hyperacetylation results in an increase in the number of DSBs (Karagiannis et al, 2005).…”
Section: Mechanisms Of Hdac Inhibitor-mediated Enhanced Radiation Senmentioning
confidence: 97%
“…The common theme is a synergistic effect following treatment of cells with HDAC inhibitors and subsequent irradiation. Mechanisms including modulation of cellcycle regulation, particularly G1-phase arrest, inhibition of DNA synthesis and apoptosis, have been identified to explain this phenomenon (Zhang et al, 2004b;Karagiannis et al, 2005;Nome et al, 2005). Clearly these are important mechanisms underlying radiation sensitization by HDAC inhibitors at relatively high doses.…”
Section: Mechanisms Of Hdac Inhibitor-mediated Enhanced Radiation Senmentioning
confidence: 99%
“…The first demonstration in 2001 that siRNA duplexes could be used in mammalian cells to suppress gene expression [6] , provided a new tool for studying gene function in mammalian cells and that may eventually be developed into gene-specific therapeutics. Since these initial reports of RNAi have emerged, it is hoped that this system can be exploited to develop a new class of drugs and numerous review articles have been published focusing on the evolution of RNAi as a therapeutic strategy [7][8][9] .…”
Section: The Rnai Pathway and Sirnamentioning
confidence: 99%
“…85 Therefore, RNAi-mediated knockdown of cancerassociated genes to inhibit tumor growth, lymphangiogenesis, metastasis, induce apoptosis and subsequently decrease the chemoradiotherapy resistance could be developed either as a stand-alone therapeutic modality or as an adjunct to conventional anticancer therapies. 13 In addition to determining the possible roles of RNAi in cancer treatment, RNAi-based therapies have been conducted to provide new alternatives for the treatment of infectious and neurologic diseases, including viral hepatitis, HIV infection and spinocerebellar ataxia. Most importantly, RNAi-based therapy has been performed in preclinical and phase I clinical trials to develop potential clinical applications of siRNA in various human diseases.…”
Section: 73mentioning
confidence: 99%